The Influence Of Problem-Based Learning Model With Inquiry Approach To Learning Outcomes Of Geography In High School - Moh. Zainuddin; Andrinata (Pesantren Reviews, 2023)
This study aims to determine the effect of a problem-based learning model with an inquiry approach to the geography learning outcomes of class X MA Darussalam Al-Kubro Moyot Islamic Boarding School Foundation, especially in the essential competencies of analyzing natural disaster mitigation and adaptation with geographical studies. The method used is descriptive quantitative. The results of the data analysis of student geography learning scores showed an increase in the average gain of the experimental class from 59.08 to 77.82, with an increase of 18.74. Although the control class also experienced an increase in score of 56.75 to 70.25 with an increase of 13.5, when compared to the experimental class, the increase in the average score of learning outcomes was higher than the increase in the control class. The difference in the increase in the score of the experimental class learning outcomes with the control is 7.57. So, the problem-based learning model with the inquiry approach significantly affects the student learning outcomes of MA Darussalam Al-Kubro Moyot. This is evidenced by the results of calculating the gain score statistic 0.4758 with a standard error of 0.02787 and a mean of 5%. The problem-based learning model with an inquiry approach can improve high school student learning outcomes. Using a problem-based learning model with an inquiry approach can develop character values of tolerance, democracy, communicativeness, self-confidence, and respect for achievement.